Chemical elements used as colour additives in cosmetic colour contact lenses and their effects on normal human corneal epithelial cells viability in vitro / Syazwan Hafiz Mohd - Mohd, Syazwan Hafiz (2021)
Purpose: The protective corneal epithelial layer can be easily compromised with unsupervised contact lens wear. The emerging popularity of cosmetic colour contact lens (Cos-CCL) wear has raised another concern about the hidden threat of colour additives used in Cos-CCL. The information on the chemical elements used as colour additives in the Cos-CCL products is scarce. Our research aimed to identify the chemical elements used as colour additives in Cos-CCLs and to investigate the effects on the human corneal epithelial cells viability. Methods: Two clusters of contact lens were studied in the controlled laboratory setting: the high water content (HWC) and the low water content (LWC). Four contact lenses (one clear contact lens and another three Cos-CCLs of different colours) were used within each cluster. Contact lens parameters such as body matrix material, water content, base curve, diameter and refractive power were standardized within each cluster comparison. Each surface orientation (front and back) of these contact lens samples were analysed using the field emission scanning electron microscope equipped with energy X-ray dispersive spectroscopy (FESEM-EDX) to identify the chemical elements on the contact lens samples. The same specification of contact lens samples was treated on the human corneal epithelial cells (HCEC) in an 8-hour time frame. The HCEC viability was assessed by MTT-assay at the end of the treatment period to acquire the effects of the contact lens samples on them. Results: FESEM-EDX examination identified five metal elements (iron, chromium, titanium, magnesium and aluminium) used in the colour additives of the Cos-CCLs, that were not found in clear contact lenses. The compositions and locations of the colour additives varied between Cos-CCLs. The HCEC viability was significantly reduced in the Cos-CCLs (p < 0.05). Clear contact lenses from both clusters showed no effect on the HCEC viability at p = 0.70 and p = 0.85 for HWC and LWC clusters, respectively. Conclusion: Cos-CCLs contained metal elements to achieve the different coloured effects in a range of coloured contact lenses. Lenses with those identified metal elements posted detrimental effect on HCEC viability in vitro. Further research is required to study the contribution of those metal elements in cosmetic colour contact lens related ocular complication under real clinical scenario.